Harvard Business Review's reframing of digital communication: From professional expertise to practical guidance - Maier, Carmen Daniela; Engberg, Jan (Journal of pragmatics, 2021)
In the context of our research work focused on mapping the latest multimodal and hypermodal strategies of constructing and communicating expert knowledge (e.g. Maier, 2014; Maier and Engberg, 2019; Engberg and Maier, 2015a, 2015b; Engberg and Maier, 2019), in this paper we address hypermodal strategies used for conveying domain-specific knowledge and offering practical guidance to various audiences. The empirical evidence is represented by a cluster of digital texts from the Harvard Business Review webpages (https://hbr.org/). This digital context aimed at communicating domain-specific knowledge and practical guidance is characterized by hypermodal communication strategies meant to accommodate various levels of expertise and interests. The paper presents and explains methodological tools suitable for investigating comprehensibility and engagement enhancement when addressing potentially non-academic receivers in a website context. For this purpose, we explore the interaction of semiotic modes as well as hypermodal combinations of the web-based genres. In this context, we aim especially at identifying the roles of the digital affordances in communicating professional expertise and practical guidance with a basis in the same Internet venue. The impact of promotional strategies is also explained. The relevance of this research work lies in its contribution to a better understanding of the complex hypermodal strategies used for reframing the communication of domain-specific knowledge to various audiences. •General focus on knowledge communication in digital environment.•Specific focus on the transition from professional expertise to practical guidance communication in Harvard Business Review.•Methodological tools for investigating comprehensibility and engagement enhancement.•Analysis of multimodal and hypermodal communication strategies in web-based genres.•Discussion of the impact of hypermodal promotional strategies in the same Internet venue.